PROTECTION OF CHILDREN’S RIGHTS IN THE DIGITAL AGE - Khilola Anvarovna Khaydarova (Bright Mind Publishing, 2026)
The article examines the protection of children’s rights in the context of the rapid development of digital technologies and the expansion of the digital environment. It analyzes the transformation of the legal nature and mechanisms of safeguarding children’s rights under conditions of digitalization, taking into account contemporary technological risks. Particular attention is paid to the application of the Convention on the Rights of the Child in the digital sphere, including the interpretation provided by General Comment No. 25 (2021) of the UN Committee on the Rights of the Child. The study identifies key digital threats affecting children, such as violations of privacy and personal data protection, cyberbullying, grooming, exposure to harmful content, and algorithmic manipulation. The role of international and regional legal instruments, as well as soft law standards developed by international organizations, is assessed. The article substantiates the necessity of strengthening the responsibility of digital platforms, implementing the principle of the best interests of the child in technological design, and developing preventive measures through digital and legal literacy. It is concluded that effective protection of children’s rights in the digital age requires a comprehensive approach combining legal regulation, institutional cooperation, platform accountability, and international collaboration.
Keywords: Children’s rights; digital environment; digitalization; privacy; personal data protection; cyberbullying; artificial intelligence; best interests of the child; international legal protection; digital literacy.